STRATEGI PENGEMBANGAN USAHATANI PADI SAWAH DI DESA SUNGAI KAKAP KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Retno Wulan Fitrianti; Erlinda Yurisinthae; Adi Suyatno (Fakultas Pertanian Universitas Tanjungpura, 2018)
This study aims to find out what priority strategy is prioritized in the development of wetland rice farming in the village of Sungai Kakap, Sungai Kakap Subdistrict Kubu Raya District. The method of analysis used in this research is descriptive method, with SWOT and QSPM analysis. Respondents in the research are experts who numbered 6 people and paddy field farmers in the village of Sungai Kakap, Sungai Kakap Subdistrict amounted to 50 people. The results of the research indicate that the strategy for the development of wetland rice farming is to develop a sustainable rice field cultivation area, implementing a system of fresh product quality assurance, human and institutional capacity building through education and training, improving farming efficiency, quality and product display, integrated pest protection, optimal utilization of resources (assets), fostering farmers and business actors with counseling and assistance in the management of farming, facilitating the establishment and development of partnership arrangements, providing up-to-date and easily accessible data and information, providing support facilities at location of development and developing self-reliance of farmers. While the priority strategy is to improve the capacity of human and institutional resources through education and training.